Analisis Budaya Makan Ronde Pada Pernikahan Etnis Tionghoa di Kota Solo - Stefany Agustine; Yohan Yusuf Arifin (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2023)
The Chinese are a minority in Indonesia, but there are still a lot of Chinese cultures that are still used in various Chinese culture celebrations, for example in weddings. Chinese marriage has a lot of step by step processions, one of which is the culture of eating “ronde”. The purpose of this research is to study about the culture of eating “ronde” in Chinese marriage in Solo City. This research will discuss about the meaning and purpose of this tradition, because at this time few Chinese couple know the tradition of eating “ronde” at their weddings. This journal uses qualitative  research methods and using interview to collect data. The tradition of eating “ronde” is believed to strengthen the relationship between both family. This concept is symbolized by ronde’s round and sticky surface that’s believed to strengthen family’s relationship, but people’s understanding of this culture still varies from one person to another. This is caused by cultural shift that happens in our society, so that tradition of eating “ronde” began to disappear in Chinese culture. Hopefully the results of this research can be used as a medium to introduce Chinese culture and references for similar research.Keywords - Chinese ethnic, Marriage, Ronde, Solo City.